Rebel Girls awesome entrepreneurs : 25 tales of women building businesses /: 25 tales of women building businesses. (2022) - Sher, Abby; Parvis, Sarah; Brew-Hammond, Nana Ekua; Sinclair, Carla; Daniel, Susanna
No abstract available